BAYANG-BAYANG IBNU ‘AṬIYAH DALAM TAFSĪR AL-BAḤRU AL-MUḤĪṬ KARYA ABŪ ḤAYYĀN AL-ANDALŪSĪY - Anam, Saichul (ojs.unsiq.ac.id, 2024)
This article intends to examine the form of influence of Abū Ḥayyān al-Andalusīy (d. 745 AH) on Ibn 'Aṭiyah (d. 542 AH) in his interpretive work al-Baḥr al-Muḥīṭ fī al-Tafsīr. This research uses qualitative methods through library studies using Gadamer's influence theory approach. Data sources in the article include primary sources and secondary sources. The primary data source is the main material object in the research, namely Al-Baḥru al-Muḥīṭ fī Tafsīr by Abū Ḥayān al Andalusīy and tafsir Al-Muḥarrar al-Wajīz. This article starts from an assumption that influence in a tradition of thought is a necessity that cannot be denied. Every thought is always in the shadow of certain situations and conditions which can form patterns of thinking and reading of texts, or in Gadamer's theory what is called an awareness of historical influence. This paper finds that Abū Ḥayyān's interpretation is heavily influenced by Ibn 'Aṭiyah in several aspects, ranging from methodology to substance. This conclusion came after the author traced these two interpretations and found that this influence could be seen in aspects of the use of history, language, qiraat, and Islamic law.